1980
DOI: 10.1038/sc.1980.61
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the neurological evolution of 300 spinal cord injuries seen within 24 hours after injury

Abstract: Abstract. A grouped Franco-Swiss study on 300 cases of spinal cord injury gives an overall view of the neurological evolution of the spinal cord injuries or cauda equina lesions. The importance of initial and repeated examinations is stressed. Sensory sparing distant to the lesion is of great importance, especially that of pain. A great number of patients showing neurological progress was observed at the end of the first month and at the beginning of the following three months. The influence of steroids is ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The reason for this difference is not known and further studies are needed. However, studies show that in cervical region injuries, more recovery is observed compared to thoracic region injuries (65)(66)(67)(68)(69), which might be due to the number of live and active axons being present in cervical regions following injury.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The reason for this difference is not known and further studies are needed. However, studies show that in cervical region injuries, more recovery is observed compared to thoracic region injuries (65)(66)(67)(68)(69), which might be due to the number of live and active axons being present in cervical regions following injury.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Treatment with methylprednisolone (MP) has been found to diminish both the disturbance in spinal cord function and the extent of the tissue damage after spinalcordinjuryincats(13,14),dogs (15), and monkeys (16). However, in large multicenter trials in humans no beneficial effect of MP on the neurological outcome has been observed (17,18). This indicates that the animal models used do not optimally mimic the different pathophysiological components that are present in the clinical situation ic man.…”
mentioning
confidence: 99%